Rebar corrosion and its interaction with concrete degradation in reinforced concrete sewers. (1st September 2020) - Song, Yarong; Wightman, Elaine; Kulandaivelu, Jagadeeshkumar; Bu, Hao; Wang, Zhiyao; Yuan, Zhiguo; Jiang, Guangming
Abstract: Concrete corrosion, as a major issue in sewer management, has attracted considerable research. In comparison, the corrosion of reinforcing steel bar (rebar) is not well understood. Particularly, fundamental knowledge of rebar corrosion and its interactions with concrete corrosion/cracking is largely lacking. This study investigated rebar corrosion and concrete degradation using reinforced concrete coupons exposed in a pilot sewer system. The physical-chemical corrosion characteristics were investigated in local regions; the nature of rebar rusts was analyzed using the advanced mineral analytical techniques, including Scanning Electron Microscope (SEM), Energy Dispersive X-ray Spectroscopy (EDS) and X-ray Diffraction (XRD); further, the interactions between rebar corrosion and concrete corrosion/cracking were elucidated by characterizing the microstructure and element distribution in interfacial areas using Mineral Liberation Analysis (MLA). The rebar corrosion products were found to be iron oxides, oxyhydroxides, chlorides, sulfides and sulfates. The predominant rebar corrosion reactions varied with exposure time and the development of concrete corrosion. When concrete corrosion reached rebar surface, the cracking of the concrete cover was influenced by multiple effects, including the macro-cracking induced by the corrosion products expansion, and the micro-cracking accelerated by the dissolution, diffusion and deposition of Fe derived from rebar rusts at the concrete corrosion front. A conceptual model elucidating rebar corrosion and the complex interactions between rebar corrosion and concrete degradation is proposed to support the development of corrosion prevention and refurbishment strategies for reinforced concrete sewers. Graphical abstract: Image 1 Highlights: A thorough investigation of rebar corrosion in reinforced concrete sewers. Interactions between rebar corrosion and concrete degradation. Rebar rusts and interfacial analysis by mineral analytical techniques. Rebar corrosion varied with time and the development of concrete corrosion. Concrete cracking induced by rebar corrosion in macro- and micro-levels.